Improving Organisational Performance Through Human Resource Management Practices Among Jordanian Civil Service: A Case Study Of Greater Amman Municipality - Mahmoud, Mo’men Hani Mohammad (2022)
Human resource management is a significant resource for improving public organisations’ performance under the implementation of new public management reforms. Given that public organisations’ performance depends highly on public servants’ competencies and skills, this study adopted the resource-based view and resource dependence theory as theoretical perspectives to improve the performance of the Greater Amman Municipality as a public organisation in Jordan through human resource management practices. It also adopted thematic analysis to analyse 15 semi-structured interviews based on purposeful sampling that related to performance weaknesses with participants from Greater Amman Municipality using Van Manaen method due to poor performance of the directorate of transport and traffic. The findings revealed several issues related to the human resource practices and performance of public organisations. The findings also revealed the best human resource practices for managing employees’ performance in public organisations. The implementation gaps in the new public management reforms are presented in the findings of the study as the primary reasons for the performance weaknesses, challenges, and gaps in human resource management practices. The originality of this study in understanding the effect of new public management reforms on human resource management practices and performance.